DAMPAK PENAMBANGAN PASIR TRADISIONAL TERHADAP LINGKUNGAN DI KAWASAN KAKI GUNUNG POCO NDEKI WOLOKOLO KELURAHAN KOTA NDORA KECAMATAN BORONG KABUPATEN MANGGARAI TIMUR - Mbas, Odilia; Wulakada, Hamza Huri; Hasan, Muhammad Husain (Jurnal Geografi, 2022)
This study aims to: (1) identify the factors that influence erosion at the foot of Mount Poco Ndeki Wolokolo, Ndora City, Borong District; (2) Identify the level of erosion hazard using the USLE formula at the foot of Mount Poco Ndeki Wolokolo, Kelurahan Kota Ndora, Kecamatan Borong; (3) identify mitigation strategies in the traditional sand mining area at the foot of the Poco Ndeki mountain, Ndora City Village, Borong District. This study uses a quantitative method with sampling technique using a sampling area so that the ex-mining area is obtained which has an erosion rate of 71.0138 tons/ha/year classified as moderate erosion level. Data sources consist of primary data and secondary data collected using field observations, documentation, and measurements. Then the data is reprocessed into field data by paying attention to library sources and map overlays. The results of the field research show that: (1) the erosion factors in the research location greatly affect the physical condition of the soil condition in the ex-mining area, these factors include: rain erodibility, soil erodibility, slope length, slope slope, land cover vegetation, and land conservation. ; (2) the level of erosion hazard obtained from the estimation using the USLE formula is classified as moderate erosion rate according to the decision of the director-general of reforestation and rehabilitation No. 041/Kpst/V/1998; (3) the mitigation strategy that must be carried out on the land is conservation efforts through agroforestry methods or forest farming systems.